Ireland's heritages : critical perspectives on memory and identity - McCarthy, Mark, Dr (Heritage, culture, and identity., 2017)
This book is the first sustained attempt to incorporate critical scholarship and thought at the cutting edge of contemporary geography, history and archaeology into the burgeoning field of Irish heritage studies. It seeks to illustrate the validity of multiple depictions of the Irish past, showing how scrutiny of heritage practices and meanings is so essential for illuminating our understanding of the present. Examining Ireland's heritages from a critical perspective that celebrates notions of heterogeneity and uniqueness, the distinguished contributors to this book scrutinise the multiplicity of complex relations between heritage, history, memory, commemoration, economy, and cultural identity within various historical, geographical and archaeological contexts. Using several examples and case studies, this book raises issues not only from a uniquely Irish perspective, but also investigates the memorialisation and marketing of the Irish past in overseas locations such as the USA and Australia.